Systemic risk of tender failures in government projects: An FMEA-based analysis of price deviation impacts on infrastructure preparedness - Mirnayani; Tyasa, Elvando Genta (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: Infrastructure preparedness during disasters depends greatly on the successful and timely execution of government construction projects, particularly multi-story buildings that function as critical public facilities. However, in practice, many of these projects experience tender failures due to significant price deviations from the Owner’s Estimate (HPS), either through underpricing or overpricing. These failures often result in delays or cancellations, disrupting the availability of essential infrastructure in emergency scenarios. Methods: This study applies the Failure Mode and Effect Analysis (FMEA) method to systematically identify, assess, and prioritize the underlying causes of tender failure in a government-funded multi-story building project. Data collection involved document analysis, expert validation, and structured questionnaires focusing on three key parameters: severity, occurrence, and detection of each failure mode. Findings: The results reveal two major categories of failure factors: issues related to documentation and problems in cost estimation. Documentation issues include unclear specifications and lack of expert personnel due to limited preparation time, while cost estimation problems involve insufficient market analysis, unrealistic pricing, and scheduling errors. The highest Risk Priority Numbers (RPNs) were found in the indicators “failure in offering strategy” (RPN = 22.944), “failure in prequalification” (RPN = 22.874), and “lack of expert personnel due to limited time availability” (RPN = 22.032), all of which are considered critical and indicative of systemic vulnerability in the tendering process. These critical failures highlight the potential risk they pose to infrastructure readiness, especially in disaster-prone contexts. Conclusion: Tender failures caused by price deviation pose a systemic risk to infrastructure preparedness. Reforming public procurement systems with improved risk identification and mitigation strategies—especially in document and cost estimation processes—is essential for supporting disaster-resilient infrastructure development. Novelty/Originality of this article: This study is one of the first to link FMEA-based tender risk assessment with disaster preparedness outcomes, offering a novel contribution to both construction management and resilience planning.